Redundancy in Biology and Robotics: Potential of Kinematic Redundancy and its Interplay with Elasticity - Verstraten, Tom; Schumacher, Christian; Furnemont, Raphael; Seyfarth, Andre; Beckerle, Philipp (Journal of Bionic Engineering, 2020)
Redundancy facilitates some of the most remarkable capabilities of humans, and is therefore omni-present in our physiology. The relationship between redundancy in robotics and biology is investigated in detail on the Series Elastic Dual-Motor Actuator (SEDMA), an actuator inspired by the kinematic redundancy exhibited by myofibrils. The actuator consists of two motors coupled to a single spring at the output. Such a system has a redundant degree of freedom, which can be exploited to optimize aspects such as accuracy, impedance, fault-tolerance and energy efficiency. To test its potential for human-like motions, the SEDMA actuator is implemented in a hopping robot. Experiments on a physical demonstrator show that the robot’s movement patterns resemble human squat jumps. We conclude that robots with bio-inspired actuator designs facilitate human-like movement, although current technical limitations may prevent them from reaching the same dynamic and energetic performance.
CRIS-Team Scopus Importer:2021-09-24
Keywords: bioinspired; energy efficiency; hopping robots; human physiology; redundant actuation; series elastic actuation